Effects of Flood Irrigation System on Abundance And Biodiversity of Soil Arthropods on Maize and Rice Farms in Gadau District, Bauchi State, Nigeria - Awwal Abiola, Taofeeq; Hassan, Ismail (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The human induced changes in the agricultural land (i.e., irrigation methods, tillage practices and land use changes) have profound impacts on the diversity and abundance of arthropods. Arthropods maintain soil ecosystem in variety of ways like breaking down the plant debris and dispersion of microorganisms. The present study was carried out to assess the effect of flood irrigation on the abundance and diversity of soil arthropods at two different randomly selected farms (maize and Rice farm) at Gadau, Itas/Gadau LGA, Bauchi state. Ten (10) pitfall traps fifteen (15) feet away was inserted in each farm for collection of soil arthropods. The arthropods were counted after seven two hours of installation and were taken to the laboratory for identification using physiological method. More also, the abundance of the arthropods was determined using Simpson index while their diversity was analyzed by Shannon-wiener index. The species abundance of soil arthropods were slightly higher in the old flood irrigation farm than the new flood irrigation farm. Hymenoptera formicidae constituted the highest and major proportion while others were detected in a low proportion in this decreasing order: spider, grasshopper and beetle. Although the richest soil arthropod was found in the newly constructed flood irrigation farm, this indicates that the soil arthropods diversity was not affected by the age of flood irrigation farm. Therefore, keeping in view the proven economic and easy irrigation with low energy input, the flood irrigation system can be adopted without harming soil arthropods diversity.